Encounter, story and dance: Human-machine communication and the design of human-technology interactions - Sandry, Eleanor (2018)
John McCarthy and Peter Wright argue that people “don't just use technology;” they “live with it,” which drives their decision “to suggest an approach to viewing technology as experience,” rather than theorizing people's “experience with technology” [8]. This paper takes a step back, to reconsider the potential of analyzing what people do with technology, because some technologies, in particular robots, are increasingly experienced as machine others, with which people are encouraged to collaborate, as opposed just to use. Recognizing the work of McCarthy and Wright, the paper takes the threads of experience they identify-sensual, emotional, compositional and spatio-temporal-and examines these alongside a broad communication-theoretical approach that identifies three interlocking elements in human-robot interactions: encounter, story and dance [11]. This framework is identified as one approach being developed within a new area of communication studies, Human-Machine Communication (HMC). The paper argues that attending to the detail of how humans and robots communicate in relation to encounters, stories and dances, supports recognition of the complexities of experience within human-robot interactions that support flexible modes of human-robot collaboration. In particular, this framework is open to the potential of machine-like robots in human-robot interactions for which a process of “tempered anthropomorphism” supports meaningful communication with a robot that is nonetheless clearly recognized by people as a machine other [11].